Recognition and Marginalization: The Paradox of Legal Politics in Indigenous Constitutional Rights in West Kalimantan - Karolin Margaret Natasa; Abdul Mukti Ro’uf; Sopian Lubis; Abu Bakar Munir (Journal of Law and Legal Reform, 2026)
Despite the constitutional guarantees provided by the Indonesian State to recognize and respect the existence of indigenous communities, the implementation of these rights remains problematic. In West Kalimantan, a province rich in both cultural diversity and natural resources, a sharp contradiction exists: while legal frameworks for recognition are expanding, indigenous peoples continue to face systematic marginalization, particularly regarding land tenure and ancestral domain. This study aims to analyze the legal-political paradox in which formal state recognition often serves as a mechanism of exclusion rather than empowerment. It seeks to uncover the underlying factors that cause legal instruments to fail to protect indigenous constitutional rights, against the backdrop of large-scale extractive industries and bureaucratic hurdles. This research employs a qualitative socio-legal approach. Data were gathered through a combination of normative legal research—analyzing constitutional mandates, national laws, and local regulations (Perda)—and empirical observations of land disputes and administrative recognition processes in West Kalimantan. The findings reveal that the “paradox of recognition” is driven by two primary factors: first, overly complex administrative requirements for legal status that transform a fundamental right into a “state-granted” privilege; and second, the dominance of developmentalist agendas that prioritize investment over indigenous sovereignty. Consequently, legal recognition in West Kalimantan often serves as a “formal mask” that stabilizes state authority while indigenous communities remain vulnerable to displacement and criminalization. The study concludes that true constitutional protection requires a paradigm shift from a state-centric recognition model to a rights-based approach that honors the self-identification of indigenous peoples.